POTENTIAL USE OF BIO-DYES FOR GREEN COLORING OF MEDICAL TEXTILES - COCÎRLEA Maria Denisa; COMAN Andrei; POPOVICI Lucia-Florina; OANCEA Simona; COMAN Diana (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork)
Cotton is a textile material frequently used in the medical system. The possibility of using natural extracts for coloring biotextiles is a current way of giving sustainability attributes to articles used in medicine. The influence of five different classical mordants and biomordants (citric acid, tannic acid, ferrous sulfate II, copper sulfate and ferrous sulfate with oxalic acid), by meta-mordanting and dyeing by exhaustion and sonication methods with Rhus typhina L. fruit extract, was evaluated. The investigation was carried out by measuring the chromatic coordinates, water and dry rubbing resistance, as well as measuring the FT-IR absorption spectra. The mixture between ferrous sulfate and 4% oxalic acid produced, according to the ATR-FTIR analysis, the greatest changes in the cotton structure, but significantly reduces the color changes resulting from the simple use of sulfate. The promising obtained results such as low color changes when using biomordants, good resistance to water and friction, encourage to continue the research regarding the application of this extract in the friendly technology of cotton dyeing.